Cytotoxic, anti-proliferative and apoptotic effects of zerumbone on human and mouse leukemic cell lines - Hamid, Asmah (2010)
Zerumbone (ZER), is a sesquiterpene isolated from the edible plant Zingiber zerumbet Smith or locally known as lempoyang. It is used in local traditional medicine as a cure for swelling, sores and loss of appetite. In this study, the cytotoxic effect of ZER was tested against different types of cell lines including leukemia cells such as WEHI- 3B (mouse myelomonocytic leukemia), HL-60 (human promyelocytic leukemia), CEM-SS (human T-lymphoblastic leukemia) and K-562 (human chronic myelogenous leukemia/ erythroleukemia), using the standard MTT assay. Results obtained showed that ZER was a potent cytotoxic agent to all leukemic cell lines tested with CD50 below 10 μg/ml after 72 hours of exposure. The morphological observation of the cell lines tested using light microscope, revealed the apoptosis feature of the treated cells such as membrane blebbing, cell shrinkage, and formation of apoptotic bodies. WEHI-3B cells were then chosen as a model in the study of cell death mechanism as the cells were also used to induce leukemia in the in vivo study. The mode of cell death determined using acridine orange/propidium iodide (AOPI) staining and Annexin V-FITC flow cytometry technique further confirmed the apoptotic effect of ZER with nuclear condensation and other apoptotic features clearly seen and the increased percentage of apoptotic cells (p<0.001) as compared to control and Doxorubicin (DOX) treated cells. The effect of ZER on the proliferation of leukemia cells was determined using MTT assay and the effect on cell cycle was identified using flow cytometry propidium iodide (PI) staining technique. Results showed that cell proliferation was inhibited at 48 hour of exposure and the cell cycle was arrested at G1/S phase followed by apoptosis. The increased percentage of hipodiploid cells in the sub-G1 phase of the cell cycle (p< 0.001) compared to control also indicated the involvement of apoptosis. The biochemical confirmation of cell death was done by analyzing the ZER treated DNA in agarose gel electrophoresis, whereas the involvement of executioner caspase-3 was also determined. The formation of DNA ladder confirmed the mode of cell death was through apoptosis mechanism and this was paralleled with caspase-3 activation found in ZER treated cells. The detection of gene expression involved in cell death was done using the MPCR (multiplex polymerase chain reaction) method, in which the expression of Bcl- 2 and Bax genes in ZER treated cells further supported the apoptosis mechanism involved in ZER action. Furthermore, in order to evaluate the effectiveness of ZER in combating leukemia, the leukemic-induced mice were then treated with 10 mg/kg and 20 mg/kg body weight of ZER. The in vivo results showed that ZER has the capability of preventing the adverse effect of leukemic cells on the treated mice such as damaged to vital organs and able to maintain the white blood cells status compared to the untreated leukemic mice. Therefore, it can be concluded that ZER exhibited its antileukemic effect through apoptosis induction, capable of preventing the spreading of leukemia cells in leukemic-induced mice, and safe to be used as an antileukemia agent as it does not affect the blood profile or damaged to the vital organs.